Construction Of Sexuality And Sexual Violence Among Alumni Of Islamic State University Of Banjarmasin, Indonesia - Kana Karina (International Journal of Sociology of Religion, 2024)
In acts of sexual violence, the wearing of the headscarf is often exploited, so it is important to do research. This study uses qualitative which is a library research. Primary data is obtained from interviews, while secondary data is obtained from journals, books, articles, and online sites. The results of the study show that the forms of construction of jilbab sexuality and sexual violence involve several aspects, such as the jilbab which is interpreted as a symbol of submission, social identity, and expression space that is often exploited. This dynamic then triggers the occurrence of sexual violence, which is influenced by patriarchal culture, the authority of the female body, and power inequality. The results of the study also show the implications of this construction of sexuality on the repression of women's bodies, the occurrence of discrimination, and the normalization of violent behavior.